2022
DOI: 10.7717/peerj.12975
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of brain natriuretic peptide vs. nicorandil in preventing contrast-induced nephropathy: a network meta-analysis

Abstract: This study aimed to conduct a network meta-analysis (NMA) to compare the efficacy of brain natriuretic peptide (BNP) vs nicorandil for preventing contrast-induced nephropathy (CIN). Databases of Pubmed, Cochrane, Embase, Web of Science were searched by keywords for eligible studies of randomized controlled trials investigating different agents (BNP, nicorandil, nitroglycerin, intravenous saline) for preventing CIN. The outcomes included a change in serum creatinine level at 48 h and the incidence of CIN after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…Previous studies have demonstrated that the incidence of CIN uctuates from 6-22% in patients undergoing primary PCI [1][2][3][4] , and in our study, the incidence of CIN in the placebo group was more than 20%. Although the mechanism of CIN is not fully understood, it is believed that this complication is closely related to renal ischemic injury and the direct renal tubular cytotoxicity of contrast medium 15 .…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Previous studies have demonstrated that the incidence of CIN uctuates from 6-22% in patients undergoing primary PCI [1][2][3][4] , and in our study, the incidence of CIN in the placebo group was more than 20%. Although the mechanism of CIN is not fully understood, it is believed that this complication is closely related to renal ischemic injury and the direct renal tubular cytotoxicity of contrast medium 15 .…”
Section: Discussionsupporting
confidence: 58%
“…CIN is associated with prolonged hospitalization, increased risk of adverse cardiovascular events, as well as short-and long-term mortality [1][2] . Some studies are exploring effective prevention for CIN [3][4][5] . To assess the efficacy of nicorandil for CIN prevention in patients with ST-segment elevation myocardial infarction (STEMI) undergoing primary PCI, we analyzed a multi-center prospective randomized controlled trial, which explored the effects of nicorandil administration on infarct size in patients with STEMI treated with PPCI (primary PCI) 6 .…”
Section: Introductionmentioning
confidence: 99%